Solid-State 13C NMR Spectroscopy Applied to the Study of Carbon Blacks and Carbon Deposits Obtained by Plasma Pyrolysis of Natural Gas - Freitas, Jair C. C.; Cipriano, Daniel F.; Zucolotto, Carlos G.; Cunha, Alfredo G.; Emmerich, Francisco G. (Journal of Spectroscopy, 2016)
Solid-state 13C nuclear magnetic resonance (NMR) spectroscopy was used in this work to analyze the physical and chemical properties of plasma blacks and carbon deposits produced by thermal cracking of natural gas using different types of plasma reactors. In a typical configuration with a double-chamber reactor, N2 or Ar was injected as plasma working gas in the first chamber and natural gas was injected in the second chamber, inside the arc column. The solid residue was collected at different points throughout the plasma apparatus and analyzed by 13C solid-state NMR spectroscopy, using either cross polarization (CP) or direct polarization (DP), combined with magic angle spinning (MAS). The 13C CP/MAS NMR spectra of a number of plasma blacks produced in the N2 plasma reactor showed two resonance bands, broadly identified as associated with aromatic and aliphatic groups, with indication of the presence of oxygen- and nitrogen-containing groups in the aliphatic region of the spectrum. In contrast to DP experiments, only a small fraction of 13C nuclei in the plasma blacks are effectively cross-polarized from nearby 1H nuclei and are thus observed in spectra recorded with CP. 13C NMR spectra are thus useful to distinguish between different types of carbon species in plasma blacks and allow a selective study of groups spatially close to hydrogen in the material.